Konsolidacja na rynku OFE a reguły konkurencji - Kostecka-Jurczyk, Daria (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article deals with the competition on the open pension funds market. The aim of the paper is to analyze competition provisions regulating this market and effects of consolidation of open pension funds in the light of competition rules. The article is based on the hypothesis that on the open pension funds market in Poland unilateral effects appear.
Keywords: Open Pension Funds; competition between OPF; market structure OPF